Decline in Health Status of Extremely Premature Neonates with Patent Ductus Arteriosus after Second Course of Medical Therapy - Knott, E. Marty; Zamora, Alvaro; Cavett, Clinton; Wattsman, Terri-ann (European Journal of Pediatric Surgery, 2013)
Introduction Many neonatal centers offer surgical ligation of patent ductus arteriosus (PDA) after two failed courses of pharmacologic therapy. This study compares health status of extremely premature (< 28 weeks gestation) neonates who failed medical therapy at the time of their second course of medical treatment versus operation.Materials and Methods A retrospective chart review was performed on neonates born at less than 28 weeks gestation who underwent PDA ligation after two rounds of medical therapy over a 7.5-year period. Measurements of health status at the time of the second course of medical therapy and the time of operation were compared.Results Neonates (n = 34) required less fraction of inspired oxygen (33.5 ± 12.9% vs. 48.5 ± 24%, p < 0.0001), had lower mean airway pressure (7.5 ± 1.9 vs. 9.1 ± 2.4 mm Hg, p < 0.0001), and were less likely to require vasopressor support (16.7 vs. 60%, p = 0.0126) at the time of the start of second course than at surgery.Conclusion Our study suggests that extremely premature neonates show a decline in cardiopulmonary reserve between a second course of medical therapy and surgical intervention.
Keywords: extremely premature; neonate; patent ductus arteriosus; ligation; cardiopulmonary reserve